(untitled) (Journal of Educational Management, 2000)
This study which was a descriptive survey, was basically to find out the factors that affected the completion of the masters thesis at the University of Cape Coast (UCC), Ghana. The primary purpose of the research was to identify factors that might be hindering masters degree students from completing their theses, thereby either delaying or forgoing the successful completion of the degree. The participants in this study were "Successful Thesis Graduates" (STGs), "All-But Thesis" students (ABTs) who were enrolled between the years 1989 and 1993 and lecturers who served as thesis supervisors within the same period. The five most significant factors identified as obstacles to completion of the thesis in order ofimportance were : (1) lack ofbooks and other relevant materials; (2) lack of financial resources; (3) students’ lukewarm attitude or lack of seriousness; (4) supervisors’ delay in vetting work submitted by students; (5) students’ work demands or combining thesis work with other jobs.